Vocational Education Curriculum: Between Vocational Education and Industrial Needs - Hani Rosina; Virgantina Virgantina; Yahyaa Ayyash; Vina Dwiyanti; Sutthiporn Boonsong (Universitas Pendidikan Indonesia (UPI), 2021)
This study aims to describe curriculum development in vocational education based on the development of Information Technology and the needs of the industrial world. This study used the literature review method from scientific articles in ten years (from 2011 to 2021) using several specific keywords to obtain the data needed. The results of this study showed that vocational schools in Indonesia need to form graduates who have soft skills and hard skills that have a match or conformity with the business and industries. Thus, vocational education graduates when entering the real world will not have difficulties adapting to the development of technology in the industry. Based on this study, any incompatibility in the community and special skills can be avoided through the implementation of a vocational education curriculum.